1991
DOI: 10.1088/0022-3727/24/7/008
|View full text |Cite
|
Sign up to set email alerts
|

On plasma sheaths surrounding complex shapes as measured using ion acoustic waves

Abstract: Experiments on the transient or ion-matrix sheath from 90 degrees convex and concave corners and randomly perturbed objects have been performed. Equiphase contours of ion acoustic waves launched from metallic structures yield results that are in substantial agreement with a numerical simulation and, for the case of the corners, with recent numerical investigations. Differences can be attributed, in part, to inhomogeneities found in the experimental plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
(3 reference statements)
1
12
0
Order By: Relevance
“…This local region of charge non-neutrality adjacent to the pulsed electrode has been given the name transient sheath or ion-matrix sheath. In preliminary experiments, it was suggested that this sheath tended to pull away from a concave corner and would crowd around a convex corner (Lim et al 1991). This was in agreement with a related numerical study of the sheath (Donnelly and Watterson 1989).…”
Section: Introductionsupporting
confidence: 84%
“…This local region of charge non-neutrality adjacent to the pulsed electrode has been given the name transient sheath or ion-matrix sheath. In preliminary experiments, it was suggested that this sheath tended to pull away from a concave corner and would crowd around a convex corner (Lim et al 1991). This was in agreement with a related numerical study of the sheath (Donnelly and Watterson 1989).…”
Section: Introductionsupporting
confidence: 84%
“…This was also noted in numerical and experimental studies of the transient sheath at 90 • corners. (Donnelly and Waterson 1989;Lim et al 1991;Sheridan and Alport 1994b).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the twocomponent sheath expansion is directly related to the earlier transient or ion-matrix sheath calculations and ion acoustic wave experiments. 8,10 In the simulations, the ion density profiles were observed to remain constant during the earliest time interval ⌬t ϭ (0 ϩ Ϫ 0), where t ϭ 0 is the time when the voltage step was applied and t ϭ 0 ϩ is the next time step. During this initial time interval, the electrons were ''blown'' into the ambient plasma leaving the transient or ion-matrix sheath behind.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In the ion acoustic wave applications, the front of the expanding two-dimensional rarefactive sheath could evolve into an ion acoustic wave. [10][11][12] In the PSII process, these ions would be the ions that are to be implanted into the electrode. This absorptions of ions results in a rarefaction in the positive ion density profiles surrounding the electrodes.…”
Section: A Uniform Electrode-two Component Plasma ‫)0؍⑀(‬mentioning
confidence: 99%
See 1 more Smart Citation